Proceso de atención de enfermería en prematuro de 4 días con síndrome de dificultad respiratoria. - Moreira Vera, Jennifer Julissa (2021)
The present clinical case was elaborated through a 4-day-old premature man who is hospitalized in the neonatal intensive care unit area with a definitive medical diagnosis of respiratory distress syndrome. However, it is vitally important to mention that respiratory distress syndrome is a pulmonary condition that will produce respiratory failure in a person that will be caused by a deficiency in alveolar surfactant, and that it is associated with an immaturity of the lung structure . In most of the thousands of cases, it has a higher incidence in premature newborns under 34 weeks of gestation (Barquet, Ramírez, & Ortega, 2016). For the diagnosis, a radiological study of the thorax will be carried out in relation to the antecedents and the clinical examination of the patient's medical history. Although we must mention that the most significant picture of respiratory distress is the disease called hyaline membrane (HMS) or respiratory distress due to surfactant deficiency (Cotallo, Sastre, & Colomer, 2018). The nursing care process was elaborated with the sole purpose of being able to contribute to the restoration of the patient's health and well-being. Therefore, the methodology implemented was aimed at a brief investigation about the risk factors that influence a newborn being born with these complications. What are the causes that trigger this pathology and the clinical manifestations. As well as the ideal and essential treatment to treat this disease (Cotallo, Sastre, & Colomer, 2018). Once all the patient's CH was analyzed and the dysfunctional patterns to be treated were determined. The care plan was carried out according to the taxonomies Nanda, nic and noc, which served as an instrument for me. Managing to take the patient to a satisfactory and successful recovery throughout their hospital stay.